The First Language Interference toward Students’ English Speaking as Foreign Language - Tania Syafutri; Andri Saputra (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2021)
This research aims at analyzing the first language interference toward students’ English speaking as foreign language made by sixth semester students in course design subject, such as phonological interference (pronunciation), grammatical (morphological and lexical), and lexical interference (vocabulary), and the factors that caused interference of the first language. This research is descriptive qualitative. The findings of the research explained that students made three types of interference categorized as phonological interference such as pronounce the word incorrectly (vowel, diphthong, consonan, and allophonic variation), grammatical interference such as in morphological (singular-plural agreement) and syntactical (subject-verb agreement, phrase, comparative adjective, possessive adjective, and parallel structure), and lexical interference such as in vocabulary (combining between Indonesian and the English language). The data showed that students often make error in phonological aspect. The factors that caused first language interference are lack of knowledge, Indonesian transfer, and lack of vocabularies of foreign language that mastered by students or respondents.